Damage Induced to DNA and Its Constituents by 0–3 eV UV Photoelectrons. (25th November 2021) - Liu, Chaochao; Zheng, Yi; Sanche, Léon
Abstract: The complex physical and chemical interactions between DNA and 0–3 eV electrons released by UV photoionization can lead to the formation of various lesions such as base modifications and cleavage, crosslinks and single strand breaks. Furthermore, in the presence of platinum chemotherapeutic agents, these electrons can cause clustered lesions, including double strand breaks. We explain the mechanisms responsible for these damages via the production 0–3 eV electrons by UVC radiation, and by UV photons of any wavelengths, when they are produced by photoemission from nanoparticles lying within about 10 nm from DNA. We review experimental evidence showing that a single 0–3 eV electron can produce these damages. The foreseen benefits UV‐irradiation of nanoparticles targeted to the cell nucleus are mentioned in the context of cancer therapy, as well as the potential hazards to human health when they are present in cells. Abstract : UV photoelectrons of 0–3 eV emitted from nanoparticles lying within about 10 nm from DNA in the cell nucleus can break bonds in the molecule. Such DNA‐damaging electrons can be produced by UV radiation of any wavelength, whereas in absence of nanoparticles damage occurs only for UVA photons. The combination of UV radiation with nanoparticles thus presents a health hazard. Conversely, it could be used in therapeutic treatments, e.g., by targeting the nanoparticles to the nucleus of cancer cells.